2018
DOI: 10.1377/hlthaff.2017.0714
|View full text |Cite
|
Sign up to set email alerts
|

Medicare Advantage Enrollees More Likely To Enter Lower-Quality Nursing Homes Compared To Fee-For-Service Enrollees

Abstract: Unlike fee-for-service (FFS) Medicare, most Medicare Advantage (MA) plans have a preferred network of care providers that serve most of a plan’s enrollees. Little is known about how the quality of care MA enrollees receive differs from that of FFS Medicare enrollees. This article evaluates the differences in the quality of skilled nursing facilities (SNFs) that Medicare Advantage and FFS beneficiaries entered in the period 2012–14. After we controlled for patients’ clinical, demographic, and residential neighb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
62
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 64 publications
(72 citation statements)
references
References 33 publications
3
62
0
Order By: Relevance
“…Medicare Advantage plans may restrict the hospitals available to patients in their networks,9 leading to both the highestand lowest-quality hospitals being less likely to be included in networks. A similar trend has been found for skilled nursing facilities 3. If higher-quality hospitals demand higher reimbursement rates, MA plans may avoid contracting with such hospitals, thereby excluding them from the network.…”
supporting
confidence: 66%
“…Medicare Advantage plans may restrict the hospitals available to patients in their networks,9 leading to both the highestand lowest-quality hospitals being less likely to be included in networks. A similar trend has been found for skilled nursing facilities 3. If higher-quality hospitals demand higher reimbursement rates, MA plans may avoid contracting with such hospitals, thereby excluding them from the network.…”
supporting
confidence: 66%
“…It is of policy interest that there does not appear to be any impact on patient health outcomes. Previous work has found that beneficiaries enrolled in MA contracts tend to enter lower quality nursing homes than those in FFS (Meyers, Mor, and Rahman ) as measured by both readmissions rates, and nursing home compare star ratings. Other work has also found that these star ratings and readmissions rates are related to patient health outcomes.…”
Section: Discussionmentioning
confidence: 98%
“…The concentration of a particular MA contract in a given SNF is determined by the admissions of FFS patients and MA patients from different plans along with patients’ length of stay and switching between Medicare plans. For instance, Meyers, Mor, and Rahman () found that MA enrollees are receiving care in lower quality of SNFs implying that higher MA concentration may reflect lower quality care. To address this in part, we include SNF characteristics, including the overall share of MA and star rating in our model; however, contract‐specific concentration may still capture unobserved SNF quality.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Prior work found that MA plan enrollees received less intense post‐acute care from a smaller number of SNFs, with lower rates of hospital readmission and higher rates of return to the community . However, there is also evidence that the SNFs used by MA enrollees are of lower quality than those used by traditional fee‐for‐service Medicare patients . Moreover, MA enrollees using SNFs or home health care were more likely to switch back to traditional Medicare the next year, potentially signaling dissatisfaction with the quality of care .…”
mentioning
confidence: 99%